CORRELATION AND PATH ANALYSIS IN POTATO (SOLANUM TUBEROSUM L.) - Regassa, Dereje; Basavaraja, N. (Potato Journal, 2013)
The experiment involving 100 potato genotypes was laid out in a simple square lattice (10x10) design with two replications at Dharwad, during kharif season of 2001 on black soils. From the results it could be noticed that tuber yield was highly and positively correlated both at phenotypic and genotypic levels with plant height, plant spread, weight of medium size tubers, weight of large size tubers, total tuber weight, number of medium size tubers, number of large size tubers and total number of tubers per plant. The correlation coefficients were highly significant (p=0.01) indicating the presence of strong association and hence it could be possible to improve the tuber yield by considering these traits. Highly significant and negative correlation was found between yield and days to flowering both at phenotypic and genotypic levels. There was a positive association between number of main stems per plant and tuber weight, tuber number, plant height and plant spread which in turn are highly correlated with yield. Seven out of eight genotypes, had a positive direct influence on the yield. However, plant spread and weight of small tubers per plant had negative direct influence only at genotypic level. Plant height has been observed to exert negative direct effect both at phenotypic and genotypic levels regardless of its positive and higher correlation with the yield both at phenotypic and genotypic levels. Weight of large size tubers per plant exerted the maximum positive direct effect on tuber yield at both phenotypic and genotypic levels followed by weight of medium size tubers per plant. The maximum positive indirect effect was exerted on yield by number of main stems per plant through weight of large size tubers per plant at genotypic level. This was followed by plant height and plant spread through weight of large size tubers per plant both at phenotypic and genotypic levels.